2015
DOI: 10.2478/raon-2014-0046
|View full text |Cite
|
Sign up to set email alerts
|

The cost of systemic therapy for metastatic colorectal carcinoma in Slovenia: discrepancy analysis between cost and reimbursement

Abstract: Background.The aim of the study was to estimate the direct medical costs of metastatic colorectal cancer (mCRC) treated at the Institute of Oncology Ljubljana and to question the healthcare payment system in Slovenia.Methods.Using an internal patient database, the costs of mCRC patients were estimated in 2009 by examining (1) mCRC direct medical related costs, and (2) the cost difference between payment received by Slovenian health insurance and actual mCRC costs. Costs were analysed in the treatment phase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Indirect costs for neutropenia, such as costs associated with patient work loss, caregiver work loss, paid caregiver and/or non-revenue-generating support centers, were estimated to be $US 3.834-$US 5.738 per episode (2006 values $US 4.741-$US 8.781), thus representing approximately 34-44% of the total cost of managing neutropenia ( 12 ). Study published in 2009 reported that one of the most common reasons for cancer patient hospitalization was FN resulting in average hospitalization of 12,9 days and inquiring significant costs ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indirect costs for neutropenia, such as costs associated with patient work loss, caregiver work loss, paid caregiver and/or non-revenue-generating support centers, were estimated to be $US 3.834-$US 5.738 per episode (2006 values $US 4.741-$US 8.781), thus representing approximately 34-44% of the total cost of managing neutropenia ( 12 ). Study published in 2009 reported that one of the most common reasons for cancer patient hospitalization was FN resulting in average hospitalization of 12,9 days and inquiring significant costs ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“… 7 Data from large observational studies, subgroup analysis and pooled analysis of randomized trials have suggested that the survival benefits associated with the use of bevacizumab in the first-line treatment are similar in elderly and general population. 8 - 13 With the introduction of bevacizumab as standard of care for mCRC patients in Slovenia 14 , our centre has created patient registry to prospectively assess patient selection as well as efficacy and safety of bevacizumab containing chemotherapy in routine clinical practice. This registry enabled data capturing of the mCRC management in geriatric population that is usually excluded in clinical research and comparison of clinical outcomes to their younger counterparts.…”
Section: Introductionmentioning
confidence: 99%